A Solar-Blind Ultraviolet Photodetector With Graphene/MgZnO/GaN Vertical Structure - Wang, Zhao; Lin, Jun; Wei, Xuan; Zheng, Wei; Hu, Qichang (Frontiers in Materials, 2021)
Graphene (Gr) has high transmittance to ultraviolet (UV) light and high mobility, which can effectively collect and transfer carriers. In this work, MgZnO (MZO) films were grown on the surface of the p-GaN by magnetron sputtering. A heterojunction solar-blind UV detector with Gr/MZO/GaN structure was constructed by introducing Gr as the window layer film. The test results show that the device has excellent detection ability for solar-blind UV light. The light response cut-off edge of the device is 263 nm, under the illumination of 255 nm and the bias voltage of -5 V, the responsivity is 14.6 mA/W, the rise time is 0.79 s, the decay time is 0.2 s, and the external quantum efficiency is 71.1%. The importance of this work lies in providing a reference for the application of Gr-based photodetectors.